(untitled) (Journal of the College of Basic Education, 2023)
This study was conducted in Ibn- Albetar specialized Hospital for Cardiovascular Disease / Baghdad from December 2011 to April 2012. Sera of 71 person of both sex aged (33-67) years, include 51 patients diagnosed with Cardiovascular disease (CVD), and 20 healthy volunteers, were used to estimate some biochemical parameters which include lipid profile (TCh,TG,HDL,LDL,VLDL) and CRP. The risk factor Atherogenic Index of Plasma (AIP) was calculated. None of the control were atherosclerotic vascular disease, diabetic, renal disease, history of allergy, alcoholic consumption and heavy smoker. Sera of the samples were divided into: 1-Control group: includes (20) healthy (both sex), ages range (25-63) years, with no previous diseases which may interfere with the parameters analyzed in this study. 2-Patients with ages ranged (33-67) years were divided into three groups according to Body Mass Index (BMI): a- Group (1): includes (11) patients (both sex) with BMI (20-24.9) Kg/m?. b- Group (2): includes (28) patients (both sex) with BMI (2-29.9) Kg/m?. c- Group (3): includes (12) patients (both sex) with BMI (30 to over) Kg/m?. The data of this study reveled a significant increase in the levels of TCh, TG, LDL, VLDL and AIP value, while a significant decrease in HDL level in sera of CVD patients compared to control. Also CRP showed significant increase in CVD patients groups as compared to control group. For BMI the results showed a significant increase in CVD for G2 and G3 while G1 showed a significant decrease as compared to control group. These results showed a significant correlation between the risk factor AIP and the parameters studied in CVD.